Volume 2C: Turbomachinery 2015
DOI: 10.1115/gt2015-43300
|View full text |Cite
|
Sign up to set email alerts
|

Open Rotor Design Strategy: From Wind Tunnel Tests to Full Scale Multi-Disciplinary Design

Abstract: For several years, Safran has been involved in the design and optimization of contra rotating open rotors. This innovative architecture is known for allowing drastic reduction in fuel burn, but its development is facing complex technological challenges such as acoustics, aerodynamics, and weight penalty due to the mechanical complexity of an Open Rotor. Since 2010, Safran has been developing the experimental test bench HERA (1/5 mock-up scale) to improve the understanding of the complex aerodynamics and acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Safran in France has been developing CRP for a number of years, both direct-drive and geared engines. Various levels of multi-disciplinary design and optimisation [122] have produced extremely complex blade geometries that are swept radially and axially; the new blades look like flags in the wind shown in Fig. 4.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…Safran in France has been developing CRP for a number of years, both direct-drive and geared engines. Various levels of multi-disciplinary design and optimisation [122] have produced extremely complex blade geometries that are swept radially and axially; the new blades look like flags in the wind shown in Fig. 4.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…While propeller optimization primarily centers on aerodynamics and aeroacoustics, structural integrity is commonly considered as a constraint [8,9]. However, structural deformations significantly impact aerodynamic performance.…”
Section: Introductionmentioning
confidence: 99%
“…According to the accident report, the blade disintegration and subsequential crash of Vertical Aerospace's prototype during the 22 nd test flight is most likely due to a degradation of a bonding within the internal blade structure [12]. Unfortunately, some research groups solely implemented static strength requirements in their routines [8,9,13]. Fatigue, frequency response, and aeroelastic instabilities are also mandatory for a vital design [14-16], even though not all of them can be estimated by reduced order methods.…”
Section: Introductionmentioning
confidence: 99%
“…Gur and Rosen additionally demonstrated that implementing geometric and structural constraints regarding stress limits within a propeller optimization routine impacts the optimized propeller layout and operating conditions [11]. Modern approaches include structural or aeroelastic constraints in multidisciplinary optimization schemes [12].…”
Section: Introductionmentioning
confidence: 99%